Ternary assembly of g-C3N4/graphene oxide sheets /BiFeO3 heterojunction with enhanced photoreduction of Cr(VI) under visible-light irradiation. (February 2019) - Hu, Xinjiang; Wang, Weixuan; Xie, Guangyu; Wang, Hui; Tan, Xiaofei; Jin, Qi; Zhou, Daixi; Zhao, Yunlin
Abstract: A novel ternary composite of graphitic carbon nitride (g-C3 N4 )/graphene oxide (GO) sheets/BiFeO3 (CNGB) with highly enhanced visible-light photocatalytic activity toward Cr(VI) photoreduction is prepared and characterized. The characterization and photocatalysis experiments corroborate its reasonable band gap, efficient charge separation and transfer, widened visible-light adsorption, easy solid-liquid separation, good stability and superior catalytic activity of CNGB. Three CNGB samples with different ratios of g-C3 N4 and BiFeO3 (CNGB-1, -2, -3 with 2:4, 3:3, and 4:2, respectively), though possessing different adsorption ability, eventually remove all Cr(VI) ions via photocatalysis within 90 min. The catalytic efficiency of the composite is the highest at pH 2; increases in pH decrease the catalytic ability. The inorganic anions such as SO4 −, Cl −, and NO3 − only slightly affects the photocatalytic process. The matching of the band structure between BiFeO3 and g-C3 N4 generates efficient photogenerated electron migration from the conduction band of g-C3 N4 to that of BiFeO3, which is also facilitated by the electron bridging and collecting effects of GO, and holes transfer from the valence band of BiFeO3 to that of g-C3 N4, yielding the efficient separation of photogenerated electron-hole pairs and the subsequent enhancement of photocatalytic activity. The research provides a theoretical basis and technical support for the development of photocatalytic technologies for effective application in wastewater treatment and Cr-contaminated water restoration. Highlights: g-C3 N4 /graphene oxide/BiFeO3 (CNGB) ternary assembly is easily prepared. CNGB shows excellent photocatalysis of Cr (Ⅵ) reduction and easy removal from water. CNGB shows maximized efficiency at low pH. CNGB have little chance of electron-hole recombination. CNGB shows great visible-light response.